Thermal insulation coating as well as preparation method and application thereof
By using the co-solvent to treat hollow glass microbeads and combining with specific emulsions, the paste-like glass microbeads are formed, which solves the problems of the aerogel coating film being prone to cracking and dust pollution, and achieves efficient thermal insulation and environmentally friendly coating preparation.
Patent Information
- Application Number
- CN202411661757.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-04
AI Technical Summary
Existing aerogel coatings are prone to cracking the paint film during use, and hollow microbeads are prone to dust pollution in the workshop, affecting the environment and the safety of operators.
The hollow glass beads are treated with cosolvents to prepare paste-like glass beads, and combined with specific types of emulsions to form coatings including emulsions, aerogel materials, paste-like glass beads, cosolvents and additives.
It achieves good thermal insulation effect of the paint, improves the stability of the paint film, reduces dust pollution, and is green and environmentally friendly.
Smart Images

Figure BDA0005143582130000041 
Figure BDA0005143582130000051 
Figure BDA0005143582130000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a thermal insulation coating and a preparation method and application thereof. Background Art
[0002] Aerogel is a new nano-scale material. Its microstructure is a porous structure of 30-50nm composed of 3-5 SiO2 nanoparticles in space. This nanostructure gives it strong thermal insulation, light weight, and long service life. Compared with traditional thermal insulation materials, aerogel's thermal insulation performance is 2-8 times that of traditional materials, and its replacement cycle is more than 10 years longer than that of traditional thermal insulation coatings. It also has a high fireproof rating, a wide operating temperature range, and a waterproof effect. Therefore, it has gradually become an important substitute for traditional thermal insulation coatings.
[0003] However, the high specific surface area of aerogels can easily cause paint film cracking. The use of anti-cracking emulsions or fibers does not improve paint film cracking, and reducing the amount of aerogels will affect the thermal insulation effect of the coating. Although there are studies on using hollow microspheres to reduce and disperse the shrinkage stress of the coating and thus improve paint film cracking, the improvement effect is still limited, and hollow microspheres will float in the open environment of the workshop, which is prone to dust pollution and is very harmful to the environment and operators.
[0004] Therefore, there is an urgent need to provide a coating which has good thermal insulation effect, is green and environmentally friendly, and the prepared coating is not easy to crack. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art. Specifically, the present invention provides a coating which has good thermal insulation effect, is green and environmentally friendly, and the prepared coating is not easy to crack.
[0006] The inventive concept of the present invention is as follows: the coating of the present invention comprises an emulsion, an aerogel material, a paste-like glass microsphere, a cosolvent, and an additive; the paste-like glass microsphere is obtained by treating hollow glass microspheres with a cosolvent; the emulsion is selected from any two of styrene-acrylic emulsion, pure acrylic emulsion, and silicone-acrylic emulsion. The present invention uses a specific type of emulsion and treats the hollow glass microspheres with a cosolvent, so that the coating has a good heat insulation effect, and the prepared coating is not easy to crack, and can also improve the dust pollution problem, which is green and environmentally friendly.
[0007] Therefore, a first aspect of the present invention provides a thermal insulation coating.
[0008] Specifically, the thermal insulation coating includes emulsion, aerogel material, paste-like glass microspheres, cosolvents, and additives;
[0009] The paste-like glass microspheres are obtained by treating hollow glass microspheres with a co-solvent;
[0010] The emulsion is selected from any two of styrene-acrylic emulsion, pure acrylic emulsion and silicone-acrylic emulsion.
[0011] Preferably, the aerogel material is a paste-like aerogel material.
[0012] Preferably, the aerogel material includes at least one of silicon-based aerogel paste, carbon-based aerogel paste and sulfur-based aerogel paste.
[0013] Further preferably, the aerogel material is a silicon-based paste-like aerogel.
[0014] Preferably, the paste-like glass microspheres include 90-99 parts of hollow glass microspheres and 1-10 parts of co-solvents, based on weight. More preferably, the paste-like glass microspheres include 95-99 parts of hollow glass microspheres and 1-5 parts of co-solvents, based on weight.
[0015] Preferably, the composition of the hollow glass microspheres includes alkali silicate.
[0016] Preferably, the co-solvent includes at least one of propylene glycol, ethylene glycol, alcohol ester dodecahydrate and alcohol ester hexahydrate.
[0017] Specifically, the co-solvent in the coating and the co-solvent in the paste-like glass microspheres both include at least one of propylene glycol, ethylene glycol, alcohol ester dodecahydrate, and alcohol ester hexahydrate.
[0018] Preferably, the auxiliary agent includes at least one of a dispersing wetting agent, a thickening agent, a defoaming agent, a pH regulator and a bactericide.
[0019] Preferably, the wetting and dispersing agent includes at least one of an ammonium salt dispersant and a nonionic wetting and dispersing agent.
[0020] Preferably, the ammonium salt dispersant includes Nopco SN5027, and the nonionic wetting dispersant includes Clariant SF8.
[0021] Preferably, the thickener comprises at least one of a cellulose thickener and an alkali swelling thickener.
[0022] Preferably, the cellulose thickener includes at least one of Ashland 250HBR and Ashland HE10K.
[0023] Preferably, the alkali swelling thickener includes Dow Chemical ASE60.
[0024] Preferably, the defoaming agent includes at least one of a mineral oil defoaming agent and a silicone defoaming agent.
[0025] Preferably, the pH adjuster includes at least one of a multifunctional amine pH adjuster and an organosilicon pH adjuster.
[0026] Preferably, the multifunctional amine pH adjuster includes Dow AMP-95, and the silicone pH adjuster includes Wacker BS-16.
[0027] Preferably, the coating also includes water, and by weight, the coating includes 18-33 parts of emulsion, 4.5-22 parts of aerogel material, 14-28 parts of paste glass microspheres, 4.5-11 parts of cosolvent, 0.9-5.5 parts of additive, and 9-60 parts of water.
[0028] Further preferably, the coating also includes water, and by weight, the coating includes 20-30 parts of emulsion, 5-20 parts of aerogel material, 15-25 parts of paste-like glass microspheres, 5-10 parts of cosolvent, 1-5 parts of additive, and 10-54 parts of water.
[0029] The second aspect of the present invention provides a method for preparing the thermal insulation coating described in the first aspect of the present invention.
[0030] Specifically, the preparation method of the thermal insulation coating comprises the following steps:
[0031] The coating is prepared by mixing various raw material components.
[0032] Preferably, the method for preparing the thermal insulation coating comprises the following steps:
[0033] (1) mixing the emulsion, the auxiliary agent, the cosolvent and water to obtain a first mixture;
[0034] (2) Mixing the aerogel material, the paste-like glass microspheres and the first mixture obtained in step (1) to prepare the coating.
[0035] Further preferably, the method for preparing the thermal insulation coating comprises the following steps:
[0036] (1) mixing the emulsion, a cosolvent, water, a pH adjuster, a wetting and dispersing agent, a portion of a thickener, and a portion of a defoaming agent to obtain a first mixture;
[0037] (2) mixing the aerogel material, the paste-like glass microspheres and the first mixture obtained in step (1) to obtain a second mixture;
[0038] (3) Mixing the remaining thickener, the remaining defoamer and the second mixture obtained in step (2) to prepare the coating.
[0039] Preferably, the preparation method of the paste-like glass microspheres is to mix the hollow glass microspheres and a solvent to obtain the paste-like glass microspheres.
[0040] Further preferably, the preparation method of the paste-like glass microspheres is to add the co-solvent in the form of a spray into the hollow glass microspheres and mix, stirring and moistening while adding, and continuing to stir after the addition is completed to obtain the paste-like glass microspheres.
[0041] A third aspect of the present invention provides a thermal insulation material.
[0042] Specifically, the thermal insulation material includes a coating formed by the coating described in the first aspect of the present invention.
[0043] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0044] (1) The present invention uses a co-solvent to treat the hollow glass microspheres to obtain the paste-like glass microspheres; the emulsion is selected from any two of styrene acrylic emulsion, pure acrylic emulsion and silicone acrylic emulsion. By using a specific type of emulsion and using a co-solvent to treat the hollow glass microspheres, the coating has an extremely low thermal conductivity, can well replace traditional thermal insulation materials, achieve good thermal insulation effects, and has good stability. The prepared coating is not easy to crack. At the same time, it can also improve the dust pollution problem and is green and environmentally friendly.
[0045] (2) The hollow glass microspheres in the present invention have been processed into a paste state, and do not require high-speed dispersion during the production process, so the preparation process is simpler. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a comparison chart of the high temperature storage stability of the coatings prepared in Example 1 and Comparative Example 2 of the present invention;
[0047] Figure 2 This is a diagram showing the appearance of the hollow glass microspheres of the present invention and the paste-like glass microspheres-1 in Example 1;
[0048] Figure 3 This is a comparison diagram of the appearance of the coatings prepared by the coatings of Example 1 and Comparative Example 1 of the present invention;
[0049] Figure 4 This is an appearance diagram of a coating prepared by the paste-like glass microspheres-C1 and the coating of Comparative Example 4 in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0050] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0051] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0052] The raw material components and amounts of the thermal insulation coatings of Examples 1-4 of the present invention are shown in Table 1.
[0053] Table 1: Raw material components and dosages of thermal insulation coatings of Examples 1-4 (parts by weight)
[0054]
[0055]
[0056] In Table 1, “ / ” means no addition.
[0057] The raw material components and amounts of the paste glass beads-1, paste glass beads-2, paste glass beads-3, and paste glass beads-4 in Examples 1-4 are shown in Table 2.
[0058] Table 2: Raw material components and amounts (parts by weight) of paste glass microbeads-1, paste glass microbeads-2, paste glass microbeads-3, and paste glass microbeads-4 in Examples 1-4
[0059] Components Paste glass beads-1 Paste glass beads-2 Paste glass beads-3 Paste glass beads-4 Hollow glass microspheres 97 95 97 96 Propylene glycol / 5 / / Ethylene glycol 3 / / / Alcohol ester twelve / / 3 / Hexadecyl alcohol ester / / / 4
[0060] In Table 2, “ / ” means no addition.
[0061] Example 1
[0062] A thermal insulation coating, the raw material components and usage are shown in Table 1, and the raw material components and usage of the paste glass microsphere-1 are shown in Table 2.
[0063] A method for preparing a thermal insulation coating comprises the following steps:
[0064] (1) under low-speed stirring, the emulsion, the cosolvent, the cellulose thickener 250HBR, the ammonium salt dispersant SN5027, the pH adjuster AMP-95, and half the amount of the polydimethylsiloxane silicone defoamer were added to pure water, and stirred for 5 minutes to obtain a first mixture;
[0065] (2) adding the aerogel paste material and the glass microbead paste-1 to the first mixture obtained in step (1), stirring at a low speed for 10 minutes until the mixture is uniform, to obtain a second mixture;
[0066] (3) Adding the alkali swelling thickener ASE60 and the remaining half amount of the polydimethylsiloxane silicone defoamer to the second mixture obtained in step (2), adjusting the viscosity to a suitable state, and obtaining a thermal insulation coating.
[0067] The preparation method of the paste-like glass microspheres-1 comprises the following steps:
[0068] The hollow glass microspheres were put into a reaction kettle, and the auxiliary solvent ethylene glycol was added under low-speed stirring, and the mixture was stirred for 30 minutes under low-speed stirring to mix evenly to obtain a paste of glass microspheres-1.
[0069] Example 2
[0070] The raw material components and amounts of the thermal insulation coating of Example 2 are shown in Table 1, and the raw material components and amounts of the paste glass microsphere-2 are shown in Table 2.
[0071] The preparation method of the thermal insulation coating comprises the following steps:
[0072] (1) under low-speed stirring, the emulsion, the cosolvent, the cellulose thickener 250HBR, the ammonium salt dispersant SN5027, the pH regulator AMP-95, and half the amount of the polydimethylsiloxane silicone defoamer were added to pure water, and stirred for 5 minutes to obtain a first mixture;
[0073] (2) adding the aerogel paste material and the glass microbead paste-2 to the first mixture obtained in step (1), stirring at a low speed for 10 minutes until the mixture is uniform, to obtain a second mixture;
[0074] (3) Adding the alkali swelling thickener ASE60 and the remaining half amount of the polydimethylsiloxane silicone defoamer to the second mixture obtained in step (2), adjusting the viscosity to a suitable state, and obtaining a thermal insulation coating.
[0075] The preparation method of the paste-like glass microsphere-2 comprises the following steps:
[0076] The hollow glass microspheres were put into a reaction kettle, and the co-solvent propylene glycol was added under low-speed stirring, and the mixture was stirred for 30 minutes under low-speed stirring to mix evenly to obtain paste-like glass microspheres-2.
[0077] Example 3
[0078] The raw material components and amounts of the thermal insulation coating of Example 3 are shown in Table 1, and the raw material components and amounts of the paste glass microspheres-3 are shown in Table 2.
[0079] The preparation method of the thermal insulation coating comprises the following steps:
[0080] (1) under low-speed stirring, the emulsion, the cosolvent, the cellulose thickener 250HBR, the ammonium salt dispersant SN5027, the pH regulator AMP-95, and half the amount of the polydimethylsiloxane silicone defoamer were added to pure water, and stirred for 5 minutes to obtain a first mixture;
[0081] (2) adding the aerogel paste material and the glass microbead paste-3 to the first mixture obtained in step (1), stirring at a low speed for 10 minutes until the mixture is uniform, to obtain a second mixture;
[0082] (3) Adding the alkali swelling thickener ASE60 and the remaining half amount of the polydimethylsiloxane silicone defoamer to the second mixture obtained in step (2), adjusting the viscosity to a suitable state, and obtaining a thermal insulation coating.
[0083] The preparation method of the paste-like glass microsphere-3 comprises the following steps:
[0084] Put the hollow glass microspheres into a reaction kettle, add the co-solvent alcohol ester twelve under low-speed stirring, and stir for 30 minutes under low-speed stirring to mix evenly to obtain paste-like glass microspheres-3.
[0085] Example 4
[0086] The raw material components and amounts of the thermal insulation coating of Example 4 are shown in Table 1, and the raw material components and amounts of the paste glass microsphere-4 are shown in Table 2.
[0087] The preparation method of the thermal insulation coating comprises the following steps:
[0088] (1) under low-speed stirring, the emulsion, the cosolvent, the cellulose thickener 250HBR, the ammonium salt dispersant SN5027, the pH regulator AMP-95, and half the amount of the polydimethylsiloxane silicone defoamer were added to pure water, and stirred for 5 minutes to obtain a first mixture;
[0089] (2) adding the aerogel paste material and the glass microbead paste-4 to the first mixture obtained in step (1), stirring at a low speed for 10 minutes until a uniform state is obtained to obtain a second mixture;
[0090] (3) Adding the alkali swelling thickener ASE60 and the remaining half amount of the polydimethylsiloxane silicone defoamer to the second mixture obtained in step (2), adjusting the viscosity to a suitable state, and obtaining a thermal insulation coating.
[0091] The preparation method of the paste-like glass microsphere-4 comprises the following steps:
[0092] Put the hollow glass microspheres into a reaction kettle, add the co-solvent alcohol ester twelve under low-speed stirring, and stir for 30 minutes under low-speed stirring to mix evenly to obtain paste-like glass microspheres-4.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses an equal amount of water to replace the paste glass microsphere-1, and the rest is the same as Example 1.
[0095] Comparative Example 2
[0096] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses an equal amount of acrylic elastic emulsion to replace the styrene acrylic emulsion and the pure acrylic emulsion, and the rest is the same as Example 1.
[0097] Comparative Example 3
[0098] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses equal amounts of styrene-acrylic emulsion and pure acrylic emulsion to replace the paste glass microsphere-1, and the rest is the same as Example 1.
[0099] Comparative Example 4
[0100] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, an equal amount of water is used to replace the auxiliary solvent ethylene glycol to prepare the paste glass microspheres to obtain the paste glass microspheres-C1, and the rest is the same as Example 1.
[0101] Comparative Example 5
[0102] The comparative example is a commercially available product, and its main raw material components and usage amounts are: 30 parts by weight of styrene-acrylic emulsion and 15 parts by weight of aerogel.
[0103] Performance Testing
[0104] 1. Coating storage stability test
[0105] The storage stability of Examples 1-4 and Comparative Examples 1-5 was tested, and the test items and test methods were as follows:
[0106] Storage stability at room temperature: Store the coating at 21℃-25℃ for 4 weeks and observe whether the appearance and viscosity are abnormal;
[0107] High temperature storage stability: Store the coating at 50-60°C for 4 weeks and observe that there is no obvious abnormality in appearance and viscosity;
[0108] Low temperature storage stability: Store the coating at 2-8°C for 4 weeks and observe the appearance and viscosity for no obvious abnormality.
[0109] Freeze-thaw cycle stability: Place the coating at -5±2℃ for 18h, then take it out and place it at 23±2℃ for 6h. Freeze and thaw three times, and observe the appearance and viscosity to find no obvious abnormalities.
[0110] The coating appearance is mainly observed for caking, stratification and deterioration; the viscosity is measured by a viscometer.
[0111] The storage stability results of the coatings of Examples 1-4 and Comparative Examples 1-5 are shown in Table 3.
[0112] Table 3: Storage stability of coatings of Examples 1-4 and Comparative Examples 1-5
[0113] Group Storage stability at room temperature High temperature storage stability Low temperature storage stability Freeze-thaw cycle stability Example 1 No abnormality No abnormality No abnormality No abnormality Example 2 No abnormality No abnormality No abnormality No abnormality Example 3 No abnormality No abnormality No abnormality No abnormality Example 4 No abnormality No abnormality No abnormality No abnormality Comparative Example 1 No abnormality No abnormality No abnormality No abnormality Comparative Example 2 Severe caking Severe caking Severe caking Severe caking Comparative Example 3 No abnormality No abnormality No abnormality No abnormality Comparative Example 4 With particles With particles With particles With particles Comparative Example 5 No abnormality Severe caking No abnormality No abnormality
[0114] It can be seen from Table 3 that the coating prepared by the present invention has good storage stability.
[0115] Comparative Example 2 uses an equal amount of acrylic elastic emulsion to replace the styrene acrylic emulsion and the pure acrylic emulsion, so that the storage stability of the coating of Comparative Example 2 is significantly worse than that of Example 1. This shows that the compounding of the styrene acrylic emulsion and the pure acrylic emulsion of the present invention plays an important role in the storage stability of the coating.
[0116] In Comparative Example 4, an equal amount of water was used to replace the auxiliary solvent ethylene glycol to prepare the paste glass microspheres, so that the storage stability of the coating of Comparative Example 4 was significantly worse than that of Example 1. This indicates that the selection of a specific type of auxiliary solvent in the preparation process of the paste glass microspheres of the present invention plays an important role in the storage stability of the coating.
[0117] Comparative Example 5 is a commercially available product, and its high temperature storage stability is significantly inferior to that of the coating of the present invention.
[0118] The high temperature storage stability comparison of the coatings prepared in Example 1 and Comparative Example 2 is shown in the figure Figure 1 As shown, Figure 1 Figure (a) is a diagram of the high temperature storage stability of the coating of Example 1. Figure 1 Figure (b) is a high temperature storage stability diagram of the coating of Comparative Example 2. Figure 1 It can be seen that the coating prepared by using specific styrene acrylic emulsion and pure acrylic emulsion in Example 1 of the present invention did not clump or agglomerate, and had good high-temperature storage stability, while the coating prepared by using acrylic elastic emulsion in Comparative Example 2 showed obvious clumping and agglomeration, and its high-temperature storage stability was significantly worse than that of Example 1.
[0119] In addition, the appearance of the hollow glass microspheres (before treatment) and the paste glass microspheres-1 in Example 1 is shown in the figure below: Figure 2 As shown, Figure 2 Figure (a) shows the appearance of hollow glass microspheres. Figure 2 Figure (b) shows the appearance of paste glass microsphere-1. Figure 2 It can be seen that the hollow glass microspheres are in powder form, and the paste glass microspheres-1 are in paste form.
[0120] 2. Coating performance test
[0121] The coatings of Examples 1-4 and Comparative Examples 1-5 were respectively applied to the corresponding plates and cured to form films at room temperature to obtain coatings with the required thickness, wherein the thickness was 2 mm in the initial crack resistance test, 3 mm in the low temperature crack resistance test, 2 mm in the bonding strength test, and 2 mm in the thermal conductivity test. Then, the coatings were subjected to performance tests. The test items and test methods are as follows:
[0122] Appearance: Visually inspect the coating to see if there is any cracking;
[0123] Thermal conductivity: Tested in accordance with 5.1.1 of GB / T 25261-2018;
[0124] Bond strength: Tested in accordance with 7.17 of JGT 24-2018;
[0125] Initial crack resistance: Tested in accordance with 7.8 of JGT 24-2018;
[0126] Low temperature crack resistance: Place at 5°C for 24 hours and observe whether the coating cracks.
[0127] The performance test results of the coatings of Examples 1-4 and Comparative Examples 1-5 are shown in Table 4.
[0128] Table 4: Performance test results of coatings of Examples 1-4 and Comparative Examples 1-5
[0129]
[0130]
[0131] It can be seen from Table 4 that the coating obtained by the coating of the present invention is not easy to crack, and has good initial crack resistance, low-temperature crack resistance and bonding strength. In addition, the thermal conductivity of the coating is small, and good thermal insulation effect can be achieved.
[0132] In comparative example 1, the paste glass microspheres-1 were replaced by an equal amount of water, so that the coating prepared by the coating of comparative example 1 was severely cracked, and the thermal conductivity and bonding strength could not be measured. In comparative example 3, the paste glass microspheres-1 were replaced by an equal amount of styrene acrylic emulsion and pure acrylic emulsion, so that the coating prepared by the coating of comparative example 3 had many cracks, and the thermal conductivity and bonding strength could not be measured. It shows that the paste glass microspheres prepared by the present invention play an important role in improving the crack resistance of the coating.
[0133] Comparative Example 2 uses an equal amount of acrylic elastic emulsion to replace the styrene acrylic emulsion and the pure acrylic emulsion, so that the bonding performance of the coating prepared by the coating of Comparative Example 2 is significantly worse than that of Example 1.
[0134] In Comparative Example 4, an equal amount of water was used to replace the co-solvent ethylene glycol to prepare the paste glass microspheres, so that the coating surface prepared by the coating of Comparative Example 4 had particles, and the thermal conductivity and bonding strength could not be measured. This shows that the selection of a specific type of co-solvent in the preparation process of the paste glass microspheres of the present invention can make the coating smoother and thus have good crack resistance.
[0135] Comparative Example 5 is a commercially available product, so the coating prepared by the coating of Comparative Example 5 is cracked, and the thermal conductivity and bonding strength cannot be measured.
[0136] The appearance comparison of the coatings prepared by the coatings of Example 1 and Comparative Example 1 is shown in the figure Figure 3 As shown (the coating has not been tested), Figure 3 Figure (a) is the appearance of the coating prepared by the coating of Example 1. Figure 3 Figure (b) is the appearance of the coating prepared by the coating of Comparative Example 1. Figure 3 It can be seen that the coating prepared by the coating of Example 1 is smooth and has no cracks, while the coating prepared by the coating of Comparative Example 1 has obvious cracking. The coating prepared by the coating of the present invention has good anti-cracking performance, and it also shows that the addition of paste-like glass beads can effectively improve the cracking problem of the coating.
[0137] The appearance of the coating prepared by the paste glass microsphere-C1 and the coating of Comparative Example 4 is as follows: Figure 4 As shown, Figure 4 Figure (a) is the appearance of the paste-like glass microsphere C1 in Comparative Example 4. Figure 4 Figure (b) is the appearance of the coating prepared by the coating of Comparative Example 4. Figure 4 It can be seen that the paste-like glass microbeads in Comparative Example 4 are agglomerated, so that the coating prepared by the coating in Comparative Example 4 has particles and is not smooth.
[0138] In summary, the present invention adopts a specific type of emulsion and treats the hollow glass microspheres with a co-solvent so that the coating has a lower thermal conductivity, can well replace traditional thermal insulation materials, achieves good thermal insulation effects, has good storage stability, is not easy to agglomerate, and the prepared coating is smooth and not easy to crack. At the same time, it can also improve the dust pollution problem and is green and environmentally friendly.
[0139] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A coating, characterized in that: Including emulsions, aerogel materials, paste glass microspheres, co-solvents, and additives; The paste-like glass microspheres are obtained by treating hollow glass microspheres with a solvent; The emulsion is selected from any two of styrene-acrylic emulsion, pure acrylic emulsion and silicone-acrylic emulsion.
2. The coating according to claim 1, characterized in that The aerogel material includes at least one of silicon-based aerogel paste, carbon-based aerogel paste and sulfur-based aerogel paste.
3. The coating according to claim 1, characterized in that In parts by weight, the paste-like glass microspheres include 90-99 parts of hollow glass microspheres and 1-10 parts of co-solvents.
4. The coating according to claim 1, characterized in that The co-solvent comprises at least one of propylene glycol, ethylene glycol, alcohol ester dodecahydrate and alcohol ester hexahydrate.
5. The coating according to claim 1, characterized in that The auxiliary agent includes at least one of a dispersing wetting agent, a thickening agent, a defoaming agent, a pH adjusting agent and a bactericide.
6. The coating according to any one of claims 1 to 5, characterized in that The coating also includes water, and by weight, the coating includes 18-33 parts of emulsion, 4.5-22 parts of aerogel material, 14-28 parts of paste glass microspheres, 4.5-11 parts of cosolvent, 0.9-5.5 parts of auxiliary agent, and 9-60 parts of water.
7. The method for preparing the coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: The coating is prepared by mixing various raw material components.
8. The preparation method according to claim 7, characterized in that: The following steps are involved: (1) mixing the emulsion, the auxiliary agent, the cosolvent and water to obtain a first mixture; (2) Mixing the aerogel material, the paste-like glass microspheres and the first mixture obtained in step (1) to prepare the coating.
9. The preparation method according to claim 7, characterized in that: The preparation method of the paste-like glass microspheres is to mix the hollow glass microspheres and a solvent to obtain the paste-like glass microspheres.
10. A thermal insulation material, characterized in that: A coating formed by the coating according to any one of claims 1 to 6.
Citation Information
Patent Citations
Elastic texture paint and preparation method thereof
CN102993887A
Fly ash microsphere-based fluorocarbon thermal insulation radiation coating and preparation method thereof
CN106519825A
Waterproof thermal insulation coating and preparation method thereof
CN108485431A
Heat insulation and heat preservation reflective composite coating
CN117343644A
Composite board of scratch resistance, and preparation method
CN1760025A